Le traitement des prépositions en grammaire générative - Jean-Charles KHALIFA (Corela)
On the basis of the common corpus, this paper discusses the generative approach to the prepositional domain, which is shown to include four subcategories defined by binary features : {±L} (lexical), {±F} (functional), namely semi-lexical prepositions, functional prepositions, adverbs and particles. We discuss some of the syntactic tests traditionally used to distinguish these categories, while showing how central modules in generative theory, especially the case filter and the theta role theory, may contribute to the analysis of the proposed examples.